Plasmapheresis adjusts inflammatory responses in potential kidney transplant recipients - Sadeghi, Mahmoud; Daniel, Volker; Wang, Haihao; Zeier, Martin; Schemmer, Peter; Mehrabi, Arianeb; Lahdou, Imad; Morath, Christian; Opelz, Gerhard (Transplantation, 2013)
Background - Plasmapheresis (PP) has been used in the treatment of various immunologic disorders, and its efficacy has mainly been attributed to the removal of humoral factors and autoantibodies. Besides these effects, PP may induce modifications of the cellular immunologic status, contributing to the restoration of impaired immunologic function. The effect of PP on lymphocyte subpopulations, plasma neopterin, and cytokines in renal transplant recipients was investigated in this study. - Methods - We compared pre-PP and post-PP lymphocyte subpopulations and plasma neopterin in 37, and cytokine plasma levels in 30, potential renal transplant recipients. Plasma neopterin and cytokines were measured by enzyme-linked immunosorbent assay kits, lymphocyte subsets were determined using four-color fluorescence flow cytometry. - Results - Lymphocyte subpopulation counts and ratios including CD45+:μL (P=0.005), CD3+:μL (P=0.02), CD4+DR+:μL (P=0.002), CD8+:μL (P=0.01), and CD8+DR+:μL (P=0.005) T cells; CD4+DR+:CD4+ (P=0.009) and CD8+DR+:CD8+ (P=0.0004) ratios; DR+ cells:μL (P=0.003); CD19+ B lymphocytes:μL (P=0.001); and plasma levels of neopterin (P<;0.0001), soluble interleukin-1 receptor antagonist (P<;0.0001), IL-8 (P=0.0001), and tumor necrosis factor-α (P=0.008) were significantly decreased after PP as compared with before PP. The results indicate a decrease of activated DR+, CD4+, and CD8+ T lymphocytes and B lymphocytes, and a decrease of monocyte and macrophage activation as a result of PP. - Conclusion - Based on these results, we conclude that PP not only removes antibodies from the plasma but, in addition, modulates T-lymphocyte activation and the inflammatory response by decreasing plasma proinflammatory cytokines.
Gesehen am 25.01.2022